Engineering properties and carbon footprint of ground granulated blast-furnace slag-palm oil fuel ash-based structural geopolymer concrete. (30th December 2015) - Islam, Azizul; Alengaram, U. Johnson; Jumaat, Mohd Zamin; Bashar, Iftekhair Ibnul; Kabir, S.M. Alamgir
Highlights: Normal weight and lightweight structural green concrete could be produced by using POFA and GGBS with low binder content. Manufactured sand could be used as an ideal replacement for conventional mining sand. In ambient cured conditions, 96% of the compressive strength of OPSGC could be achieved in 7 days. The usage of OPSGC could reduce the density by 20% compared to NWGC. Abstract: Engineering properties of geopolymer concrete developed using palm oil fuel ash and slag as binders, manufactured sand and quarry dust as replacement materials for fine aggregate, and oil palm shell (OPS) as coarse aggregate were investigated along with carbon footprint. The use of binder content of 425 kg/m 3 with OPS based lightweight concrete produced the highest compressive strength of 33 MPa. Ultrasonic pulse velocity of normal weight geopolymer concrete (NWGC) shows it as "good quality". The development of structural grade OPS geopolymer concrete comparable to NWGC shows its potential application for structural purposes. OPS geopolymer concrete has lower carbon footprint of 50–60% compared to conventional concrete.